On the genus Gallorhynchus Schockaert & Brunet, 1971 (Platyhelminthes, Kalyptorhynchia, Polycystididae) with the description of four new species - Schockaert, Ernest R.; Tessens, Bart S.; Gobert, Stefan; Revis, Nathalie; Artois, Tom J. (Zootaxa, 2017)
A comprehensive overview is given of the representatives of the taxon Gallorhynchus Schockaert & Brunet, 1971: the two known species G. simplex and G. mediterraneus of Schockaert & Brunet, 1971, Syltorhynchus schockaerti Noldt, 1989, which is transferred to the taxon Gallorhynchus, and four new species, G. elegans n.sp., G. faroensis n.sp., G. genista n.sp. and G. bidaformis n.sp.. G. schockaerti occurs in the North Sea; all other species were found in the western Mediterranean and in south Portugal.